Exploring teacher and school variance in students' within-year reading and mathematics growth. Issue 4 (2nd October 2019) - Anderson, Daniel
ABSTRACT: Much research has evaluated teacher- or school-level variance in students' achievement as a proxy for teacher or school effects. These effects have almost exclusively been estimated across years with state-level testing data. In this paper, interim assessment data, collected across 9 time points in the fall, winter, and spring of Grades 3 to 5 were used to model students' within-year reading and mathematics growth. A multilevel model was used to estimate growth rates within each grade while accounting for the summer transition period, and intercept and slope variance was parsed into student, teacher, and school components. Results indicated substantial variance between both teachers and schools in students' within-year growth, which complicates interpretations about each level without reference to the other.